2021
DOI: 10.1016/j.celrep.2021.110104
|View full text |Cite
|
Sign up to set email alerts
|

Defective brown adipose tissue thermogenesis and impaired glucose metabolism in mice lacking Letmd1

Abstract: Highlights d Letmd1 is a brown-fat-enriched protein induced by cold and b-adrenergic signaling d b3-adrenoreceptor-dependent energy expenditure in mice requires Letmd1 d Letmd1 loss causes abnormal brown fat mitochondria and thermogenic gene expression d Letmd1 interacts with the chromatin remodeler BRG1 to regulate thermogenic genes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…During the process of revising our manuscript, we came across several recently published reports that have also investigated the role of LETMD1 in BAT function 46 49 . While these studies consistently demonstrated the upregulation of LETMD1 in response to cold stimulation and impaired thermogenic function in Letmd1 KO mice, each report describes distinct aspects of LETMD1 function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the process of revising our manuscript, we came across several recently published reports that have also investigated the role of LETMD1 in BAT function 46 49 . While these studies consistently demonstrated the upregulation of LETMD1 in response to cold stimulation and impaired thermogenic function in Letmd1 KO mice, each report describes distinct aspects of LETMD1 function.…”
Section: Discussionmentioning
confidence: 99%
“…While these studies consistently demonstrated the upregulation of LETMD1 in response to cold stimulation and impaired thermogenic function in Letmd1 KO mice, each report describes distinct aspects of LETMD1 function. For instance, Choi et al 46 demonstrated an interaction between LETMD1 and Brg1 in the nucleus, suggesting a potential link to transcriptional regulation of BAT thermogenesis. Snyder et al 47 demonstrated that LETMD1 is essential for BAT structure and OXPHOS expression, even under thermoneutral conditions.…”
Section: Discussionmentioning
confidence: 99%
“…LETMD1 had also the largest rank at TFCP2 locus. This gene plays a role in thermogenesis of brown adipose tissue, and mice lacking this gene were susceptible to diet-induced adiposity and impaired glucose disposal 33 .…”
Section: Pnplamentioning
confidence: 99%
“…Ebf2 deficiency causes BAT developmental abnormalities although this is eventually compensated for in adult mice [ 128 ]. Recently, loss of the mitochondrial protein Letm1 domain containing 1 (Letmd1) was shown to produce severe abnormalities in BAT mitochondria and the expression of thermogenesis related genes, including UCP1, and caused the knockout mice to die from hypothermia upon cold exposure, resembling the UCP1 null mice [ 129 , 130 ]. β3-Adrenoreceptor-stimulated increases in energy expenditure are completely abolished in these mice.…”
Section: Thermogenic Adipose Tissue and Systemic Metabolismmentioning
confidence: 99%